2020
DOI: 10.15294/jhe.v5i2.30384
|View full text |Cite
|
Sign up to set email alerts
|

Personal Hygiene Practices in 5th Grade Elementary School Students

Abstract: Background: Personal hygiene is something that needs to be taken care of especially in elementary school-aged children. Data from the Srondol Community Health Center states that in 2017 the fifth-highest number of diarrhea occurred in elementary school-aged children. SDN Srondol Kulon 02 is a health promoting elementary school in the city of Semarang. Based on School Health Unit data, in 2018 there were 52 students from SDN Srondol Kulon 02 referred to the public health center because of diarrhea and 13 studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
1
1
0
5
Order By: Relevance
“…Another study conducted by Aprita & Susianawati (2023) showed that of the 34 respondents the attitude of the highest adolescents was in the good category at 70.6%, as much as 26.5% was sufficient. This research is in line with previous research which found that the results of the attitude frequency distribution showed that 54.1% of respondents had a bad attitude in personal hygiene (Nurhayati & Wuri, 2020). As many as 53.3% of young women have a negative attitude towards personal hygiene.…”
supporting
confidence: 92%
“…Another study conducted by Aprita & Susianawati (2023) showed that of the 34 respondents the attitude of the highest adolescents was in the good category at 70.6%, as much as 26.5% was sufficient. This research is in line with previous research which found that the results of the attitude frequency distribution showed that 54.1% of respondents had a bad attitude in personal hygiene (Nurhayati & Wuri, 2020). As many as 53.3% of young women have a negative attitude towards personal hygiene.…”
supporting
confidence: 92%
“…DISCUSSION Based on table 1, it shows that the degree of personal hygiene in research samples that are positively infected with STH has poor personal hygiene, this is in line with Adiningsih (2018) that the degree of personal hygiene is related to the epidemiology of helminth infections so that if personal hygiene is poor it is easy to cause helminth infections or experience positive worm infection. 7 The results of stool examination on 50 respondentsfarmer in the village of Guntung shown in table 2 and table 3 it was found that as many as 3 respondents found hookworm eggs. This is consistent with the statement that the highest incidence of hookworms is found in plantation work groups such asfarmer whose activities are in direct contact with the ground.…”
Section: )mentioning
confidence: 96%
“…7,8 Di Semarang penelitian serupa pernah dilakukan namun pertanyaan yang diajukan dalam hal pengetahuan dan sikap terhadap kebersihan diri sangat luas. 9 Sehingga dengan dilakukannya penelitian diharapkan dapat memberikan pertanyaan yang lebih terperinci dan terarah pada aspek kebersihan diri.…”
Section: Pendahuluanunclassified